ASUHAN KEBIDANAN PADA NY ”A” DENGAN PRESENTASE BOKONG GESTASI 28 MINGGU 5 HARI DI PUSKESMAS BIRU WATAMPONE KABUPATEN BONE - Hasnidar (Jurnal Suara Kesehatan, 2016)
ABSTRACT;Midwifery Care In Mrs. "A" With Gestational ass Percentage 28 Week 5 Days In Puskesmas Biru Watampone Bone regency. Aiming to be able to formulate a diagnosis / actual problems with the pregnancy, diagnosis / potential problems immediate action / collaboration at Mrs. "A" with the pregnancy breech gestation, may plan an action in midwifery care at Mrs. "A" with the pregnancy breech gestation of 28 weeks 5 days , implementing measures midwifery care at Mrs. "A" with a breech pregnancy gestation of 28 weeks 5 days, can evaluate midwifery care at Mrs. "A" with a breech pregnancy gestation of 28 weeks 5 days in Puskesmas Biru Watampone. This research method using cross sectional study with a population of 139 respondents and 58 were sampled. Sampling using systematic random sampling method. The results showed that; a). Determination of the diagnosis on the basis of determining the diagnosis performed at Mrs. "A" with a percentage of buttocks in accordance with the theory and application on a case study, the diagnosis of potential in the case of a percentage buttocks at Mrs. "A" no data to support the potential that is the potential occurrence of labor breech and diagnosis which has been upheld then the data is not there that support for immediate action. b). Any action taken has been planned to resolve the case, all the plans, has been implemented by mothers and conditioned with a case experienced by Mrs. "A", as well as the documentation is very needed because it is the responsibility and accountability on the other health workers to midwifery care has been given.